2017
DOI: 10.1080/02673843.2017.1371615
|View full text |Cite
|
Sign up to set email alerts
|

Friends’ plans for college and adolescents’ educational expectations: an instrumental variable approach

Abstract: Friends are an important influence on adolescents' educational outcomes. However, because of their similarity on numerous attributes, it is difficult to estimate whether friends influence each other, or whether they select friends who are similar to them. To address this endogeneity, this study uses instrumental variable estimation on panel data from the High School Longitudinal Study of 2009 to estimate the effect of friends' plans for college on adolescents' educational expectations. Results from two-stage l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…The absence of social network structural effects on friendship formation does not lend support to proposed educational interventions targeting expansion and diversification of adolescent peer groups as a means to raise adolescent educational expectations (Carolan, 2018). Educational interventions to promote adolescent friendship formation with peers with higher educational aspirations may not afford benefits in greater educational expectations as suggested previously (Brown et al, 1997;Kiuru et al, 2007).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The absence of social network structural effects on friendship formation does not lend support to proposed educational interventions targeting expansion and diversification of adolescent peer groups as a means to raise adolescent educational expectations (Carolan, 2018). Educational interventions to promote adolescent friendship formation with peers with higher educational aspirations may not afford benefits in greater educational expectations as suggested previously (Brown et al, 1997;Kiuru et al, 2007).…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies that link educational expectation development and adolescents' friendship formation suffer from two important methodological concerns (Carolan, 2018;Kiuru et al, 2007). First, prior studies do not control for alternative explanatory pathways by which adolescents choose or reject their friends (e.g., selection and influence).…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty of statistically disentangling peer influence from a tendency to associate with similar others has long been recognized. Some of the methods that have been attempted to resolve this issue are cross-lagged panel models [20][21][22], discrete time event history models [23], and two stage least square regression [24,25]. All of these methods, however, have inherent shortcomings, in that they do not adequately address the network dependence of the actors, they fail to consider potentially important unobserved feedback mechanisms between networks and behavior, and they do not control for alternative mechanisms that may be responsible for observed changes [26].…”
Section: Introductionmentioning
confidence: 99%
“…The 'r' value presented in the [ Table- 4], revealed that occupation of the parents showed positive, but no significant correlation with social competence level of the boy respondents at 0.01 level of significant. Weight showed negative, but nonsignificant correlation social competence level of the boy respondents at 0.05 level of significant.…”
Section: Abstract-mentioning
confidence: 99%
“…Adolescence is an essential developmental stage when multiple systems are involved in a complex process that influences their thinking and planning regarding adulthood and future expectations.The term adolescent means "to grow to maturity". A large part of the adolescent social life is built around school-related activities [1][2][3][4][5][6][7]. It is a new place where friendships are made and nurtured.…”
Section: Introductionmentioning
confidence: 99%